First Insights into the Genome of the Moderately Thermophilic Bacterium Clostridium tepidiprofundi SG 508(T) - Poehlein, Anja (Genome Announc, 2016)
The moderately thermophilic bacterium Clostridium tepidiprofundi is Gram-positive and belongs to clostridial cluster I. It was isolated from a hydrothermal vent chimney. Substrates utilized by C. tepidiprofundi include casein, peptone, tryptone, yeast extract, beef extract, starch, maltose, and glucose. The genome consists of one replicon (3.06 Mb).